Refining the material substance: Aristotle's program in Metaphysics H1-5 - Mie, Fabian Gustavo (2018)
In Met. Z17, Aristotle makes a fresh start (1041a6) in his discussion on substance. Accordingly, the substantial form is principle and cause (1041a6-10, 1041b8), whereas the matter is element (1041b31) of material substances. Besides, Aristotle assumes (probably without justifying in Z17) that material substances are unified wholes (1041b11-12). These are two main theses in Z17 whose apparent absence in the summary of H1 (1042a3-23) has raised doubts among commentators as to the very project of H a book commonly held to be a bunch of notes on Z. Regarding H?s positive results, commentators mostly focus on the introduction of the modal vocabulary of potentiality and actuality into which Z?s distinction between matter and form is translated. So they find book?s H proper contribution only in H6?s solution to the problem of unity (1045a23-25, 1045b18-19). As a consequence of this reading, H1-5 remain overshadowed by H6, and therefore they are often neglected. Contrarily to this still predominant trend towards not taking H1-5 on their own, I will here try to show that these chapters develop a program, in which H6?s conclusion is properly prepared. Stations of this program are H2-3, where Aristotle justifies the priority of form, and then H4-5, where he does the same for the unity of material compounds. So, I aim to show that H1-5 are a centerpiece in the completion and fulfilment of Z17?s theory of material substance.